Capitalism at a crossroads: A new reset? - ARI, ALİ (Springer Nature, 2023)
As the current capitalist system has been increasingly struggling to respond to the problems and uncertainties in the global economy, this book aims to identify the main economic, social, and ecological problems and discusses solutions for a more inclusive and sustainable economic system. Written by an international selection of contributors, it takes a wider perspective beyond classical orthodox economics.By doing so, this book covers a wide range of topics, such as global warming and climate change, food and energy scarcity, rising inequality and debt issues, health, ecological, economic, and political crises, degrowth, green new deals, solidarity, economy, artificial intelligence, technological change, smart solutions, and smart cities. Discussing these topics, the book presents answers to the question of whether the current capitalist system is viable and provides suggestions for a fair, inclusive, and modern economic system.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities